SEISMIC DEPTH MIGRATION FOR COMPLEX STRUCTURE IMAGING USING KIRCHHOFF METHOD - AMALIA (NIM: 12313056), NADIA
Naturally, earth is very heterogeneous both in physical features and structure. The geological structure of the earth which has dip and complex form will affect the seismic section which result in imaging the true condition of the subsurface less accurately. Steep dip reflectors will be in untrue position which will lead to misinterpretation. Then migration process has to be done in order to bring back the dip reflectors to its true position. Kirchhoff migration is one of the methods or algorithms which is commonly used in migration process because of its easy and simple implementation and ability to solve complex structure. In Kirchhoff migration, traveltime computation is a crucial part. There are some methods to solve it, amongst them are ray tracing and fast marching method. For complex structure with strong lateral velocity variation and complex nonhyperbolic moveout, Kirchhoff migration must be done in common shot gather and depth domain or prestack depth migration. In this final project, Kirchhoff prestack depth migration with ray tracing and fast marching method as a traveltime computation method are attempted to image the complex structure of the earth which is Marmousi model. Kirchhoff prestack depth migration is proven to better focus the energy so the result could be interpreted clearly. Whilst ray tracing and fast marching as traveltime computation method appear to work well in Kirchhoff migration, but fast marching method guarantees a higher accuracy .